The Effect of Organizational Culture and Leadership on Work Quality Mediated by Discipline and Job Satisfaction at the Merauke District Court - Sinaga, Pantas; Meliala, Janita S.; Ariadi, Wa (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the effect of organizational culture and leadership, on work quality mediated by work discipline and job satisfaction in the Merauke District Court. The type of research used is quantitative research through comparative causation. The population is 31 people, the sample is taken from all populations. Data collection procedures in the form of questionnaires, interviews, and literature studies. Furthermore, descriptive analysis was carried out. Path Analysis is used to test the direct effect and indirect effect. Based on the direct effect test conducted, the results show that there is an insignificant effect and a significant effect. The results of direct influence testing show that the insignificant influence is organizational culture on job satisfaction, leadership influence on work discipline, organizational culture influence on work quality and leadership influence on work quality. The indirect effect of the research variables that become mediators with significant results shows that work discipline is able to mediate or become an introduction to organizational culture to work quality. Recommendations, to increase job satisfaction at the Merauke District Court Office, it is necessary to strive through norms, habits, traditions in general in doing something in the organization as well as through characteristics as an increase in the capacity of organizational culture.